ANALYSIS OF FACTORS AFFECTING COMPANY VALUE IN THE PROPERTIES AND REAL ESTATE SECTOR IN ISSI - Husna, Rahmatul; Julian Atika, Nisya; Irawati, Chintia; Dewi, Nurmila; Raihan, Rahmi (Fakultas Ekonomi dan Bisnis Islam - IAIN Lhokseumawe, 2023)
This research aims to determine the influence of Debt to Equity Ratio, Return On Equity, Earning Per Share, Company Size and Dividend Policy either partially or simultaneously on the Value of Companies in the Properties & Real Estate Sector listed on the Indonesian Sharia Stock Index. This research was conducted using annual data from 2019 to 2021. The data used in this research is secondary data using published financial reports and accessed through the relevant company websites. The model used in this research is panel data fixed effect model, classical assumption test and hypothesis test with a significance value of 5%. The data processing was carried out using the Eviews12 analysis tool. The results show that Debt to Equity Ratio, Return On Equity, Earning Per Share and Dividend Policy partially have a significant effect on Company Value. However, partial company size does not have a significant effect on company value. Simultaneously Debt to Equity Ratio, Return On Equity, Earning Per Share, Company Size and Dividend Policy together have a significant effect on the Value of Companies in the Properties & Real Estate Sector listed on the Indonesian Sharia Stock Index.